Technical analysis of four archaeological andean painted textiles - Rebecca Summerour; Jennifer Giaccai; Keats Webb; Chika Mori; Nicole Little (Nuevo mundo - Mundos Nuevos, 2016)
This project investigates the materials and manufacturing techniques used to create four archaeological Andean painted textiles in the collection of the National Museum of the American Indian, Smithsonian Institution. The textiles are attributed to Peru but have minimal provenience. Building on previous work by other scholars on similar archaeological textiles, the materials and manufacturing techniques are identified and characterized by observation, documentation, and scientific analysis. Several analytical techniques are used to identify materials with emphasis on distinguishing between organic and inorganic colorants. Non-invasive analytical techniques, including X-ray fluorescence and fiber optics reflectance spectroscopy, as well as ultraviolet and infrared imaging techniques, were used to characterize an insect-derived pink color, blue and black indigo, and red iron earth pigments. Additional analysis with Fourier transform infrared spectroscopy, micro X-ray diffraction, and liquid-chromatography-diode array detector-mass spectrometry led to identification of carminic and ellagic acids on detached yarn fragments.